2021
DOI: 10.1039/d1nr04268h
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrasmall Prussian blue nanoparticles attenuate UVA-induced cellular senescence in human dermal fibroblasts via inhibiting the ERK/AP-1 pathway

Abstract: Ultraviolet A (UVA) irradiation can induce cellular senescence and cause skin photoaging, which is mainly driven by excessive production of reactive oxygen species (ROS). Emerging studies have focused on new...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Protein kinase Cζ (PKCζ) phosphorylates p47phox and causes membrane-translocation of p47, inducing NOX2 activation [ 32 ]. ROS promotes phosphorylation of extracellular signal-regulated kinases (ERK), a subunit of MAPKs [ 33 , 34 ]. We found that MNNG induced phosphorylation of PKCζ, p47, and ERK, which were all restrained by crocetin pre-treatment in a concentration-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Protein kinase Cζ (PKCζ) phosphorylates p47phox and causes membrane-translocation of p47, inducing NOX2 activation [ 32 ]. ROS promotes phosphorylation of extracellular signal-regulated kinases (ERK), a subunit of MAPKs [ 33 , 34 ]. We found that MNNG induced phosphorylation of PKCζ, p47, and ERK, which were all restrained by crocetin pre-treatment in a concentration-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further research and exploration of the unique properties of USPBNZs in the context of skin health are warranted and may contribute to the development of innovative strategies for skin care and anti-aging interventions. 15 2.2.2 The significance of PBNZ crystallinity. The degree of crystallization significantly influences both the size and catalytic selectivity of the enzyme activity of nanomaterials such as PBNZs.…”
Section: Ning Gumentioning
confidence: 99%
“…Further research and exploration of the unique properties of USPBNZs in the context of skin health are warranted and may contribute to the development of innovative strategies for skin care and anti-aging interventions. 15…”
Section: The Discovery and Modulation Of The Ros-scavenging Activity ...mentioning
confidence: 99%
“…Protein kinase Cζ (PKCζ) phosphorylates p47phox and causes membrane-translocation of p47, inducing NOX2 activation 31 . ROS promotes phosphorylation of extracellular signal-regulated kinases (ERK), a subunit of MAPKs 32,33 . We found that MNNG induced phosphorylation of PKCζ, p47, and ERK, which were all restrained by crocetin pre-treatment in a concentration-dependent manner (Fig.…”
Section: Crocetin Reduces the Mnng-induced Early Phase Of Oxidative S...mentioning
confidence: 99%